Destination Image and Intention to Visit the Tokyo 2020 Olympics among Hong Kong Generation Y. Issue 3 (1st October 2016) - Pratt, Stephen; Chan, Wai Sum (Amy)
ABSTRACT: Although a great deal of previous research has been done to evaluate the impact of international mega sports events on a destination image, there is a lack of empirical evidence on images that people hold of a destination before the event. The purpose of this study is to examine the relationship between destination image and the intention to travel to Japan to attend the 2020 Tokyo Olympic Games. A total of 315 surveys were collected online through the social media Facebook during the time of the 2014 Winter Olympics in Sochi, Russia. Hong Kong Generation Y's interest in attending the 2020 Tokyo Olympics is driven by destination image factors such as being a safe and clean destination and being perceived to be able to competently hold such a mega-event as well as by an interest in sports. Interest in attending the Games is negatively related to Japan being perceived as having many historical, cultural and environmental attractions. The implications of these findings are valuable to the Japan National Tourism Organization and Tokyo Olympic Organizing Committee for marketing the event.